Application of Cluster Analysis to Physico-chemical Parameters of Munj Sagar Talab, Dhar (Madhya Pradesh, India) - and Amita Dagaonkar2, Man Mohan Prakash1*, (Recent Research in Science and Technology, 2010)
Clustering technique has received attention in many areas including engineering, medicine, biology and data mining. The purpose of clustering is to group together data points, which are close to one another. In the present study, cluster analysis is applied to physico-chemical parameters of Munj Sagar Talab (water body in Dhar, M.P, and India). Cluster Analysis (CA) was used for analyzing physico-chemical data obtained from Munj Sagar Talab. Seventeen parameters (Water Temperature, pH, Dissolved Oxygen, Free Carbon Dioxide, Calcium, Magnesium, Total Hardness, Nitrates, Chloride, Alkinity, Bicarbonate Carbonate Alkalinity, Phosphate, Silicates, BOD, Depth, Transparency and Conductivity.) were measured. Samples were collected from three sampling locations. This paper illustrates the usefulness of using statistical techniques in analyzing environmental data for better understanding of the behavior of different parameters.